Differential Dependence of Levansucrase and α-Amylase Secretion on SecA (Div) during the Exponential Phase of Growth of Bacillus subtilis - Leloup, Laurence (American Society for Microbiology, 1999)
SecA, the translocation ATPase of the preprotein translocase, accounts for 0.25% of the total protein in a degU32(Hy) Bacillus subtilis strain in logarithmic phase. The SecA level remained constant irrespective of the demand for exoprotein production but dropped about 12-fold during the late stationary phase. Modulation of the level of functional SecA during the exponential phase of growth affected differently the secretion of levansucrase and α-amylase overexpressed under the control of the sacB leader region. The level of SecA was reduced in the presence of sodium azide and in the div341 thermosensitive mutant at nonpermissive temperatures. Overproduction of SecA was obtained with a multicopy plasmid bearing secA. The gradual decrease of the SecA level reduced the yield of secreted levansucrase with a concomitant accumulation of unprocessed precursor in the cells, while an increase in the SecA level resulted in an elevation of the production of exocellular levansucrase. In contrast, α-amylase secretion was almost unaffected by high concentrations of sodium azide or by very low levels of SecA. Secretion defects were apparent only under conditions of strong SecA deprivation of the cell. These data demonstrate that the α-amylase and levansucrase precursors markedly differ in their dependency on SecA for secretion. It is suggested that these precursors differ in their binding affinities for SecA.